Go Green Trash Bin - HAYAT GEN-TECH / Nur Hafiqah Ahmad Hayat - Ahmad Hayat, Nur Hafiqah (2020)
HAYAT GEN-TECH is one of the sole proprietorship undertakings manufacturing the market innovation product. The result of innovation that has been developed should meet the market needs and give the customer more benefits. One of the innovation products which HAYAT GEN-TECH will manufacture is Go Green Trash Bin. Go Green Trash Bin is a trash bin with a multifunction that separates a garbage from two different categories, such as recycler products and food waste, and then the food waste is a compost fertilizer. This trash bin is made from easy-to - clean stainless steel, solid and others. This product in innovation technology needs to operate with electricity supply. Go Green Trash Bin also a friendly user product. Households and restaurants are the target audiences for the Go Green Trash Bin. This is because restaurants and households really need the trash bin which can make waste management simpler for them. This target audience is a person who will still be using the trash bin in their everyday lives.